2016
DOI: 10.4206/agrosur.2016.v44n2-06
|View full text |Cite
|
Sign up to set email alerts
|

Control de intensidad de defoliación sobre la producción de forraje estacional y total en sistemas lecheros

Abstract: This study aimed to determine the effect of controlling the intensity of defoliation (ID) on forage production and herbage disappearance in eight commercial farms, in a complete randomized block design. Two blocks were selected in each farm to compare, the grazing management routine of the farm (T0) vs. controlled management (T1, pre grazing height 15-20 cm and post grazing height 5-7 cm). Pre grazing sward height (SH), herbage mass (HM, kg DM ha-1) and daily growth rate (GR, kg DM ha-1 d-1) were determined. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Grazing management strategies will also have direct effects on pasture growth, where low post-grazing sward heights have an unfavorable impact on pasture regrowth and on the total forage production (Chapman, 2016). In Uruguay, previous research has indicated that increasing post-grazing sward height presents benefits for both pasture and animal performances (Mattiauda et al, 2009;Zibil et al, 2016). However, studies to understand the relationships between daily dry matter intake in eating behavior and milk production of dairy cows at different residual sward height management are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Grazing management strategies will also have direct effects on pasture growth, where low post-grazing sward heights have an unfavorable impact on pasture regrowth and on the total forage production (Chapman, 2016). In Uruguay, previous research has indicated that increasing post-grazing sward height presents benefits for both pasture and animal performances (Mattiauda et al, 2009;Zibil et al, 2016). However, studies to understand the relationships between daily dry matter intake in eating behavior and milk production of dairy cows at different residual sward height management are scarce.…”
Section: Introductionmentioning
confidence: 99%